Fe xviii and Fe xx Forbidden Lines Observed by Solar Orbiter/SPICE - Peter R. Young; Andrew R. Inglis; Graham S. Kerr; Therese A. Kucera; Daniel F. Ryan (The Astrophysical Journal)
The first simultaneous observations of the Fe xviii 974.86 Å and Fe xx 721.56 Å forbidden lines from the Spectral Imaging of the Coronal Environment (SPICE) spectrograph on Solar Orbiter are presented. The lines were observed from the postflare loops of an M2.5 class solar flare that peaked at 23:49 UT on 2024 March 23. The Fe xx /Fe xviii ratio is used to derive a temperature spacetime map for the flaring period, with values ranging from 8 to 20 MK. The map reveals repeated episodes of heating at the SPICE slit location over a 30 minute period. For one location with the brightest emission, the plasma cooled from 10 to 8 MK in 5 minutes, which is longer than the expected conductive cooling time of 170 s, suggesting continued background heating during the cooling period. Doppler shifts of between 0 and +10 km s ^−1 were obtained with precisions of 1–4 km s ^−1 , but the accuracies are lower due to uncertainties over the absolute wavelength calibration; hence, we cannot conclude there are plasma flows in the flare loops. The widths of the two lines were found to be close to the instrumental widths with no evidence of nonthermal broadening although this result is limited by the instrument resolution. The Fe xviii and Fe xx lines have high signal-to-noise with only a 5 s exposure time, demonstrating that the lines will be valuable for high-cadence flare studies with SPICE.